Contested knowledge in Dutch climate change policy. (26th November 2018) - Bekkers, Victor; Van Buuren, Arwin; Edwards, Arthur; Fenger, Menno
Abstract : In dealing with wicked problems, policymakers increasingly are confronted with three competing 'knowledge claims': the notion of evidence-based policy, alternative 'commons knowledge' created by citizens, and 'fact-free' politics. Consequently, the knowledge base for dealing with wicked problems is becoming increasingly contested. This paper analyses the ways in which these three competing knowledge claims interact, and the consequences of their interaction, through a case study of the dynamics of knowledge claims in Dutch climate policy. The paper concludes that the quest for evidence-based policy may constitute an impediment to progress in finding common ground in practical policies.